Poder de suprimento de potássio de solos da zona fisiográfica de Baturité, Ceará, Brasil - Araujo Crisóstomo, I. Indbergue; Castro, Abeilard Fernando de (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A laboratory and greenhouse study was conducted with so'l samples obtained from twenty soil units in the geographical zone of Baturité, Ceará State, Brazil The quantity of potassium liberated from non-exchangeable form was determined by inten-sive cropping of coin for a period of 240 days. Potassium extracted by com plants was compared to potassium extracted by chemical extracting agents. The exhacting methods used were normal ammonium acetate solution, IN nitric acid and sulfuric acid, as suggested by Hunter and Pratt in 1937. The amount of potassium released ravied greatly among the 20 soils units Narrow correlation values were obtained between the potassium supplying power as measured by the plant and the potassium extracted by chemical methods.